PENGELOLAAN SUMBER DAYA AIR BERDASARKAN KEARIFAN TRADISIONAL: PERSPEKTIF HUKUM LINGKUNGAN - Nadia Astriani; Ida Nurlinda; Amiruddin A.Dajaan Imami; Chay Asdak (Arena Hukum, 2020)
AbstractLegal pluralism in Indonesia provides a place for indigenous peoples to manage their natural resources where their lives are based on a living philosophy that is in harmony with nature, produces a pattern of management of natural resources that is environmentally friendly and sustainable. This article focus on studying water resource management practices based on traditional wisdom carried out by indigenous peoples in Indonesia and whether the management of water resources based on traditional wisdom can be used as an example of sustainable water resource management. The results of research conducted on the Ciptagelar indigenous people, Subak practices in Bali and 9 (nine) regions in Indonesia show that the practices of water resource management carried out in these areas are in line with the approach of sustainable water resource management. Some forms of community practice can even be adopted in the management of water resources carried out by the government. Furthermore, regulation of water resources based on values that live in society is easier to implement in the life of the community itself, therefore, regulation of water resources in the future must pay more attention to the values that live in the community.Â AbstrakÂ Pluralisme hukum di Indonesia memberikan tempat bagi masyarakat adat untuk mengelola sumber daya alamnya, yang kehidupannya dilandasi falsafah hidup yang selaras dengan alam, menghasilkan pola pengelolaan sumber daya alam yang ramah lingkungan dan berkelanjutan. Artikel ini fokus pada mempelajari praktek pengelolaan sumber daya air (SDA) berdasarkan kearifan tradisional yang dilakukan masyarakat adat di Indonesia dan apakah pengelolaan SDA berdasarkan kearifan tradisional ini dapat dijadikan contoh pengelolaan SDA yang berkelanjutan. Hasil penelitian yang dilakukan pada masyarakat adat Ciptagelar, praktik Subak di Bali dan 9 wilayah di Indonesia menunjukkan bahwa praktik-praktik pengelolaan SDA di wilayah tersebut sejalan dengan pendekatan pengelolaan SDA yang berkelanjutan. Beberapa bentuk praktik masyarakat bahkan dapat diadopsi dalam penyelenggaraan pengelolaan SDA yang dilakukan oleh pemerintah. Pengaturan SDA yang berbasis nilai-nilai yang hidup di masyarakat lebih mudah diterapkan dalam kehidupan masyarakat itu sendiri, sehingga ke depan pengaturan SDA harus lebih memperhatikan nilai-nilai yang hidup di masyarakat.